Creating shared value as a framework for responsible application of artificial intelligence in Serbia - Bulatović, Gordana (Serbian Journal of Management, 2024)
This paper proposes a model of creating shared value as a framework for responsible application of artificial intelligence in Serbia, taking into account key social and economic challenges brought by this technology. The work relies on analysis of existing literature in the fields of artificial intelligence, creating shared value and Serbia’s strategies for AI development. Key challenges and opportunities related to AI application in Serbia have been identified. The proposed model of creating shared value can provide a responsible and beneficial development of the AI sector in Serbia, considering the social and economic impacts of this technology.